2016
DOI: 10.2147/cia.s101369
|View full text |Cite
|
Sign up to set email alerts
|

Fried frailty phenotype assessment components as applied to geriatric inpatients

Abstract: BackgroundManagement of geriatric patients would be simplified if a universally accepted definition of frailty for clinical use was defined. Among definitions of frailty, Fried frailty phenotype criteria constitute a common reference frame for many geriatric studies. However, this reference frame has been tested primarily in elderly patients presenting with relatively good health status.ObjectiveThe aim of this article was to assess the usefulness and limitations of Fried frailty phenotype criteria in geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Frailty is a clinical syndrome that develops following a decline in function and resilience across numerous physiological systems [8][9][10][11]. One commonly used measure of frailty is the frailty phenotype created and validated by Fried and colleagues, which provides a standardized measure based on the assessment of five criteria: unintentional weight loss, weakness, exhaustion, slowness, and low physical activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a clinical syndrome that develops following a decline in function and resilience across numerous physiological systems [8][9][10][11]. One commonly used measure of frailty is the frailty phenotype created and validated by Fried and colleagues, which provides a standardized measure based on the assessment of five criteria: unintentional weight loss, weakness, exhaustion, slowness, and low physical activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to a global rise in life expectancy, maintaining physical function and preventing disability in advanced age are among the major clinical and public health priorities 2,3. Frailty is one of the main factors that suppresses successful aging and leads to adverse health consequences, mainly falls and delirium after minor stressor 4…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the slight association of sociodemographic variables with the two dimensions suggested that this approach of frailty showed very little association with sociodemographic aspects not corroborating previous studies (Bieniek et al, 2016;Nyunt et al, 2017;Papachristou et al, 2017;Lewis et al, 2018), which should be the subject of further research, considering these two dimensions of the frailty phenotype and across different age groups. This study analyzed only the oldest old people with very low variability in education level and health condition, as referred to in the Limitations section.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies that used the frailty phenotype revealed that the proportion of frailty among oldest old individuals is particularly high (Duarte and Paúl, 2015;Bieniek et al, 2016) in comparison with younger old individuals (e.g., frailty prevalence increased with age from 31.7% in the 60-69 age group to 67.6% in the 90+ age group, and from 22.5% in the 50-65 age group to 60.4% in the 75+ age group, respectively). These results seem to indicate that the frail condition is very frequent among oldest old individuals and suggests that the frailty phenotype provides low variability within the oldest old subgroup once a large proportion of oldest old individuals are frail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation